Debate: The Constitutionality of Stop-and-Frisk in New York City - Rosenthal, Lawrence (2013)
Stop-and-frisk, a crime prevention tactic that allows a police officer to stop a person based on “reasonable suspicion” of criminal activity and frisk based on reasonable suspicion that the person is armed and dangerous, has been a contentious police practice since first approved by the Supreme Court in 1968. In Floyd v. City of New York, the U.S. District Court for the Southern District of New York ruled that New York City’s stop-and-frisk practices violate both the Fourth and Fourteenth Amendments. Professors David Rudovsky and Lawrence Rosenthal debate the constitutionality of stop-and-frisk in New York City in light of Floyd and Judge Shira A. Scheindlin’s controversial removal from the case. Professor Rudovsky argues that Floyd shows the important role of data and statistical analysis in assessing the constitutionality of stop-and-frisk procedures. He contends that empirical evidence regarding both the factors for and outcomes of stops and frisks in New York demonstrates that either the legal standard is too permissive or police-stop documentation is not truthful. In response, Professor Rosenthal argues that Judge Scheindlin erred in failing to consider evidence of stop-and-frisk’s efficacy—evidence indicating that the NYPD’s stops are based on reasonable suspicion, a standard considerably less demanding than “preponderance of the evidence.” Additionally, Rosenthal argues that Judge Scheindlin should have considered differential offending by race or other potentially nondiscriminatory explanations for the higher stop rates of minorities